Penyuluhan Bahaya Penyebaran Berita Palsu (Hoaks) Bagi Kelompok Ibu-Ibu Pemberdayaan Kesejahteraan Keluarga (PKK) - Nisa Dwi Septiyanti; Nova Tri Romadloni; Rauhulloh Ayatulloh Khomeini Noor Bintang (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
The increase in social media users in recent years has led to an abundance of content that allows users to get new information quickly and easily. However, not all of the information obtained is correct information. Even today, a lot of fake information (hoaxes) is being spread deliberately made to achieve certain goals. In order to be wise in receiving information, it is necessary to realize the importance of media literacy. According to a survey, parents tend to spread hoax news more than young people. This is mostly done by mothers through chat which easily forwards information without reading and understanding it first. This activity aims to provide knowledge about the benefits of using social media as well as an understanding of the negative sides and dangers of hoaxes. This activity targeted PKK mothers in Jatimulyo Village, Jatipuro District, Karangnayar Regency, with 34 participants. This activity was carried out using lecture, discussion, and question-and-answer methods. It is hoped that this community service activity can help mothers navigate the various available media content so that they can make informed decisions about what they choose to consume.